2012
DOI: 10.1007/s00299-012-1231-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of alanine aminotransferase homologues by abiotic stresses in wheat (Triticum aestivum L.) seedlings

Abstract: Wheat (Triticum aestivum L.) seedlings contain four alanine aminotransferase (AlaAT) homologues. Two of them encode AlaAT enzymes, whereas two homologues act as glumate:glyoxylate aminotransferase (GGAT). To address the function of the distinct AlaAT homologues a comparative examination of the changes in transcript level together with the enzyme activity and alanine and glutamate content in wheat seedlings subjected to low oxygen availability, nitrogen and light deficiency has been studied. Shoots of wheat see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 43 publications
1
16
0
2
Order By: Relevance
“…The presence of putative light-regulation and circadian elements in the promoter regions of PnAlaAT1 and PnAlaAT2 is consistent with our data and may partially explain the expression patterns of these genes in leaves575859. Previous studies showed that both AlaAT and GGAT activities were present in etiolated wheat seedlings but their activity was half of that observed in light-grown seedlings, and exposure of etiolated seedlings to light caused an increase in enzyme activities and upregulated GGAT1 gene, while AlaAT1 gene didn’t respond60. But in our study, the expression of PnAlaAT1 and PnAlaAT2 exhibited a diurnal fluctuation in leaves (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of putative light-regulation and circadian elements in the promoter regions of PnAlaAT1 and PnAlaAT2 is consistent with our data and may partially explain the expression patterns of these genes in leaves575859. Previous studies showed that both AlaAT and GGAT activities were present in etiolated wheat seedlings but their activity was half of that observed in light-grown seedlings, and exposure of etiolated seedlings to light caused an increase in enzyme activities and upregulated GGAT1 gene, while AlaAT1 gene didn’t respond60. But in our study, the expression of PnAlaAT1 and PnAlaAT2 exhibited a diurnal fluctuation in leaves (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The elevated levels of diverse metabolites under similar conditions of stress may arise due to coregulation of biochemical pathways at the molecular level. For example, literature evidence points toward an increased accumulation of at least 15 amino acids (belonging to the primary metabolism) together with volatile organic compounds (VOCs) under drought stress (Joshi and Jander, 2009; Fraire-Velázquez et al, 2011; Gill and Tuteja, 2011; Álvarez et al, 2012; Du and Wang, 2012; Hayat et al, 2012; Kendziorek et al, 2012; Griesser et al, 2015; Hudson, 2015; Niinemets, 2015; Weldegergis et al, 2015). Additionally, it was noted that abiotic stresses like temperature and salinity could regulate the levels of other primary (sugar alcohols and sugars) and specialized (phenylpropanoids, alkaloids, etc.)…”
Section: Stress Conditions Regulating Primary and Specialized Metabolmentioning
confidence: 99%
“…(Flores and Galston, 1982; Smith, 1984; Cho et al, 1999; Streeter et al, 2001; Weise et al, 2006; Cuevas et al, 2008; Rosa et al, 2009; Gill and Tuteja, 2010; Hochberg et al, 2013, 2015; Zhao et al, 2013; Alam et al, 2014; Mouradov and Spangenberg, 2014; Zhang et al, 2014; Le Gall et al, 2015; Saleh and Madany, 2015; Sheshadri et al, 2015; Wei et al, 2015). Furthermore, biotic stress like herbivory also displayed a remarkably similar metabolite profile in plants; while primary metabolites like phenylalanine and allantoin were found to be elevated, the levels of VOCs (specialized metabolites) were also enhanced (Fraire-Velázquez et al, 2011; Du and Wang, 2012; Hayat et al, 2012; Kendziorek et al, 2012; Griesser et al, 2015; Hudson, 2015; Weldegergis et al, 2015; Takagi et al, 2016). Thus, the trend of overproduction of primary and specialized metabolites arising from diverse pathways under similar conditions of stress, further confirms the predominant role of stress as a possible link to elucidate the crosstalk between primary and specialized metabolism (Tuteja, 2007; Bolton, 2009; Qados, 2011; Bhargava and Sawant, 2013; Chamoli and Verma, 2014).…”
Section: Stress Conditions Regulating Primary and Specialized Metabolmentioning
confidence: 99%
“…The transamination between alanine and 2-oxoglutarate by alt results in the production of glutamate and pyruvate in a reversible manner, providing dual functions in carbon and nitrogen metabolism (Kendziorek et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…AlaAT has been implicated in many processes during plant development and as a stress responsive element (Diab and Limami 2016;Duff et al 2012;Good and Crosby 1989;Kendziorek et al 2012;Liepman and Olsen 2003;Miyashita et al 2007;Muench and Good 1994;Rocha et al 2010a, b;Yang et al 2015). In addition to participating in general amino acid metabolism, alt, serves as a carbon shuttle, which mobilizes pyruvate from the mesophyll to the bundle sheath cells in C4 plants (Son and Sugiyama 1992).…”
Section: Introductionmentioning
confidence: 99%